Effects of shifting political values ​​in Iraq An analytical study of the post-occupation period (Journal of the College of Basic Education, 2022)
Values ​​have always existed since human history, and there were no values ​​to the extent that we are witnessing today. Isn't one of the first results of globalization what it revealed of the diversity of cultures and the multiplicity of values ​​that we were previously ignorant of? The strangeness in the phenomenon of globalization does not lie, then, in the imaginary and feigned absence of values. However, the crisis we are going through indicates that we have lost our moral compass and are no longer able to determine the right direction. There is no crisis of values, and we have many of them, as much as there is a crisis in defining the meaning of values ​​and in the readiness and competence to manage our affairs. The question, then, is to know how we navigate between values